Thermophysical and thermal cyclic behavior of nano-enhanced molten salts for concentrated solar power - Hatem Ahmad, Mohamed Aljaerani (2023)
There are definite trends towards maximizing the utilization efficiency of solar energy through concentrated solar power (CSP) by using molten salts, which have enhanced the efficiency of CSP plants since they replaced thermal oil as heat transfer fluids (HTF) and as thermal energy storage (TES). However, these molten salts have limited TES properties. These thermophysical properties can be enhanced by adding a small amount of nanoparticles to the base salt, which may enhance the overall efficiency of the CSP systems. The purpose of this work is to characterize HITEC with various nanoparticles and assess the impact of varying nanoparticle concentrations on the thermophysical properties of the formulated Nano-Enhanced HITEC Molten Salt (NEHMS) samples. It also seeks to examine the long-term thermal cycle stability of these properties as well as to assess the impact of the improved thermophysical properties of NEHMS on electricity price and the efficiency of the CSP plant. NEHMS were synthesized using CuO, TiO2, and h-BN nanoparticles separately at different concentrations (0.1, 0.5, and 1.0 wt.%). The NEHMS samples were characterized for compatibility and nanostructure analysis. The thermophysical properties and thermal cyclic behaviour of the nano-HITEC samples were evaluated to find the optimum sample. Furthermore, the impact of improving thermophysical properties on efficiency and electricity cost was assessed. The wet preparation method was used to formulate HITEC and NEHMS samples. The compatibility of HITEC with the nanoparticles was analysed with FTIR spectroscopy. DSC was utilized to evaluate the specific heat capacity, melting point, and latent heat of HITEC and NEHMS samples. Thermal stability was measured by TGA while the characterization analysis was performed using FESEM, and EDX. The thermal cyclic stability of the optimum samples was done in this study to evaluate the stability of the enhanced properties after 100 cycles. Also, the simulation was used to examine the effect of applying the optimum samples on the efficiency of the CSP plant and the cost of producing electricity and compared the results of the optimum sample with those of the currently used HTF and TES solar salt. The results showed that 0.1wt.% nanoparticles is the optimum concentration which resulted in the best thermophysical properties enhancement. The heat capacity was enhanced by 5.6%, 27%, and 5.5%, latent heat by 30%, 72%, and 78%, and thermal stability by 9%, 7%, and 5% for HITEC with 0.1 wt.% CuO, 0.1 wt.% h-BN, and 0.1 wt.% TiO2 nanoparticles respectively. The morphological analysis revealed a good dispersion of nanoparticles in HITEC and the formation of a bright chain-like nanostructure due to nanoparticle dispersion. The FTIR showed the stability of the nanofluid mixture without any chemical reaction between HITEC and the used nanoparticles. The thermal cyclic stability showed the stability of the nanocomposite and the enhanced properties. The CSP efficiency evaluation revealed that employing the optimum sample would improve CSP plant efficiency by 1.4%, and lower power costs by 0.13 ¢/kWh. The outcomes of this research reduce the gap of finding the optimum salt for CSP systems which may result in a reduction of the electricity price and an increase in the dependency on solar energy as a clean electricity source. This study contributes to the 10-10 MYSTIE (No.1 Energy, and No.10 Environment and Biodiversity) and the 17 SDGs (No.7 Affordable and Clean Energy, and No.13 Climate Action).